Reconstruction of state territorial management to optimize national resilience in Indonesia - Puspitawati, Dhiana; Prakoso, Lukman Yudho; Kusumaningrum, Adi; Harahab, Nuddin (Faculty of Law, University of Muhammadiyah Malang, 2023)
The status of Indonesia as an archipelago state is stated clearly in the Indonesian Constitution. Indonesia’s territory consists of three dimensions: land, sea, and air. To maintain the order of the State, the State’s security is crucial. It is further argued that State’s security in all territorial dimensions can be established through a comprehensive inward-looking approach. With this approach, national security can be achieved while holding on to the principles of national resilience. In order to maintain a stable national resilience, sustainable policies are needed to govern the land, air, and ocean territory. This research analyses whether existing policies in a state’s territorial governance are sufficient to maintain national resilience. Using a multi-disciplinary approach that combines descriptive-qualitative and normative-juridical methods, this research recommends a policy model for governing the State’s territory towards maintaining national resilience in Indonesia. While the inward approach is preferable, contemporary threats to national resilience need to be considered by considering an outward-looking approach.